If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + 8) = 0 Reorder the terms: (3 + x)(x + 8) = 0 Reorder the terms: (3 + x)(8 + x) = 0 Multiply (3 + x) * (8 + x) (3(8 + x) + x(8 + x)) = 0 ((8 * 3 + x * 3) + x(8 + x)) = 0 ((24 + 3x) + x(8 + x)) = 0 (24 + 3x + (8 * x + x * x)) = 0 (24 + 3x + (8x + x2)) = 0 Combine like terms: 3x + 8x = 11x (24 + 11x + x2) = 0 Solving 24 + 11x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (8 + x)(3 + x) = 0Subproblem 1
Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {-8, -3}
| 5x+5=600 | | -4x(-x)= | | 10d+4=7d+16 | | 4(m+2)= | | 6y^2-y-12=0 | | x+8=2(x+24) | | 6(a+3)-15= | | 4(m-2)+2(3m+2)= | | 8x-16=4x-4 | | 525+0.21x=850 | | 11x+5=4x+9 | | x+6=40 | | 13(4x-7)=13 | | 8(3x+6)=96 | | 2(x+7)=56 | | s^2+s+4=0 | | 71-6x=35 | | 22+4x=50 | | y^2-4= | | 5x-73=27 | | 2Y^3-Y+3X-2=0 | | 6x+29=13x+41 | | s^2-s+4=0 | | (6x-7)+9x=68 | | 10x-117=5x-7 | | 8x^7y(5x^6y^2-6x^2+4y^3)= | | 5(2y+4)= | | -2+3(x-9)-2(x+3)=0 | | 2z^2+40=-8z | | 4+x=117 | | p+4p=60 | | 5x^2+30x-10=0 |